Sliding wear behavior of fully nanotwinned Cu alloys - Jianfeng Yan; Andrew Lindo; Ruth Schwaiger; Andrea M. Hodge (Friction)
Abstract Highly nanotwinned (NT) metals have advantages such as high strength, good ductility, favorable corrosion resistance, and thermal stability. It has been demonstrated that the introduction of high density NT microstructures can enhance the tribological properties of metals. However, the influence of the microstructure and the composition of NT alloys on the tribological behavior are not clear. In this work, the sliding wear behavior of fully NT materials, specifically Cu-Al and Cu-Ni alloys, are studied by a nanoscratch technique using a nanoindenter. The effects of microstructure and chemical composition on the wear properties are also studied. The results show that the chemical composition has an obvious influence on the wear resistance and microstructural deformation. For NT Cu-Al alloys, the hardness and sliding wear resistance improve with increased Al content from Cu-2wt.%Al to Cu-6wt.%Al. NT Cu-10wt.%Ni alloy shows even better wear resistance than Cu-6wt.%Al. The microstructural analysis shows that NT Cu alloys with higher wear resistance correspond to a smaller deformation-affected zone. The improvement of sliding wear properties of Cu-Al alloys with higher Al content may be ascribed to their decreased stacking fault energy. NT Cu-Ni alloy shows better wear resistance than Cu-Al alloy, this may be related to the formation of intermetallic compounds in Cu-Al system. This study broadens the knowledge about tribological properties of NT materials and provides a potential method to optimize their sliding wear resistance by altering the chemical composition of NT Cu alloys.